PENGARUH PENGGUNAAN MEDIA WARDWALL TERHADAP HASIL BELAJAR SISWA KELAS IV SD INPRES TUADALE KABUPATEN KUPANG - Hali, Antonius Suban; Lehan, Andriyani Afliyanti Dua; Wofsi Neolaka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is a quantitative research aimed at determining the significant influence between Wordwall media on student learning outcomes on plant body material in grade IV SD Inpres Tuadale. This research uses the Pre-Experimental design method with the form of One Group Pretest-Posttest Design. The population used in this study was grade IV students of SD Inpres Tuadale which amounted to 16 people. The sampling technique used is a saturated sample where all populations are sampled. Data collection techniques are tests, observations and document studies. This research was conducted at SD Inpres Tuadale West Kupang. Furthermore, the results showed that the normality test showed a significant value of 0.200 > 0.05 so that the data was normally distributed, the homogeneity test results showed Levene's (sig) of 0.578 > 0.05 so that the data obtained were homogeneous. The results of the hypothesis test, using paired sample T-test showed that the significance value (2-tailed) was 0.000. This shows that at the level of significance (2-tailed) < 0.05. In accordance with the basis of decision making due to the value of sig. (2-tailed) < 0.05, there is a significant influence between Wordwall media on student learning outcomes.